EKSISTENSI MASJID DI ERA RASULULLAH DAN ERA MILLENIAL - AHMAD PUTRA; PRASETIO RUMONDOR (Universitas Islam Negeri (UIN) Mataram, 2019)
This paper explains the many functions of a mosque. Muslims certainly know that the mosque at the time of the Prophet became a very vital place, not only as a place for the five daily prayers but also functioned for various kinds of activities and activities of the people. Along with the development of the millennial era and era as it is now, without us realizing the function of the mosque described by the Prophet in the past indeed the whole is not visible anymore, although some still survive today. However, the mosque in the millennial era like now the mosque is still a place that is admired for various religious activities so that the existence of the mosque still continues. Forms of functioning of the mosque in the millennial era namely, such as the Kasidah, teenage wirid, isra ’Mi'raj, mauled Prophet and other activities. With historical-theological research, the researcher aims to explain that the mosque in the millennial era did not function like the era of the Prophet, but religious activities still persist until now.